Cabelo e identidade negra : vozes, narrativas e contribuições para a educação das relações étnico-raciais - Aguiar, Josimeire Ferreira de (2021)
The research entitled - "Black hair and identity: voices, narratives and contributions to the education of ethnic-racial relations" integrates the studies carried out by NEPRE - Center for Studies and Research on Racial Relations, the study has as its object the narratives on capillary transition, in which the main objective was to understand how the hair transition (the process in which individuals stop straightening their hair) enables the construction of black identities. In this study, we interpret hair as an identity symbol, being one among other characteristics used to demarcate the difference of this ethnic/racial group in relation to the others. Among the theoretical references we can highlight: Brandão (2007), Domingues (2004, 2007), Gomes (2019), Hall (2008, 2006), Munanga (1986), Schucman (2014, 2018), Souza (1983) and Woodward (2000). The research made it possible to understand that the hair transition is a long process, in which the individual starts to learn to love their hair, to learn the necessary care, and also learns to deal with anti-black oppositions that see their strengths lose their impact on the life of those who were subservient to whiteness and its domination. In this sense, in the research we carried out, it was possible to understand that the hair transition provides the construction of black identities as this phenomenon leads to the acceptance and resignification of curly/curly hair, which was once rejected. The state of rejection points to the identity conflicts that pass through the body and the self-image that are culturally meaning based on social representations. We highlight the relevance of this study for the field of education, as it has to do with processes of construction of identities that take place in alterity in a relationship of teaching and apprehension of the constitution of being in power relations.